Self-medication among health professional during the COVID-19 pandemic (Research, Society and Development, 2023)
Introduction: Studies have shown that self-medication is a common practice in Brazil among health professionals due to the tendency to avoid looking for a specialist. However, few studies have evaluated the self-medication among these professionals during the COVID-19 pandemic scenario in Brazil. Objective: The present study investigated of self-medication among health professionals during the COVID-19 pandemic in Brazil. Methods: A cross-sectional study was fulfilled with 290 health professionals. The participants answered a pre-tested and revised questionnaire that was sent remotely to different online groups and platforms. Results: The sample of 290 healthcare professionals reported self-medication during this period. Among the drugs, the most used, 161, were analgesics and anti-inflammatories, and the most important reason that led to this practice is previous experience with the sign/symptom, mostly headache and migraine, 131 (45,2%). Conclusion: We conclude that healthcare professionals maintained high levels of self-medication during the COVID-19 pandemic, when compared to the pre-COVID-19 literature.